2020
DOI: 10.1029/2020gl090041
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally Shallow Boundary Layer Associated With Severe Air Pollution During the COVID‐19 Lockdown in China

Abstract: After the 2020 Lunar New Year, the Chinese government implemented a strict nationwide lockdown to inhibit the spread of the Coronavirus Disease 2019 (COVID-19). Despite the abrupt decreases in gaseous emissions caused by record-low anthropogenic activities, severe haze pollution occurred in northern China during the COVID lockdown. This paradox has attracted the attention of both the public and the scientific community. By analyzing comprehensive measurements of air pollutants, planetary boundary layer (PBL) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 47 publications
2
60
0
2
Order By: Relevance
“…Differences between Aeolus HLOS and RWP winds may be due to Aeolus and RWP errors and due to how RWP represents the Aeolus winds in terms of spatial and temporal aggregation. The latter will cause differences in the case of heterogenic atmospheric optical and dynamic conditions (Sun et al, 2014). We note that atmospheric heterogeneity may differ for ascending (18:00 LST) and descending (06:00 LST) Aeolus orbits due to the daily atmospheric cycle over land.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Differences between Aeolus HLOS and RWP winds may be due to Aeolus and RWP errors and due to how RWP represents the Aeolus winds in terms of spatial and temporal aggregation. The latter will cause differences in the case of heterogenic atmospheric optical and dynamic conditions (Sun et al, 2014). We note that atmospheric heterogeneity may differ for ascending (18:00 LST) and descending (06:00 LST) Aeolus orbits due to the daily atmospheric cycle over land.…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, when the aerosol scattering signal is too strong, the molecular scattering signal will be dramatically attenuated, thereby undermining the inversion of Rayleigh wind (Tan et al, 2008(Tan et al, , 2017. For instance, many previous studies have shown that China experienced several episodes of severe haze pollution during the COVID-19 lockdown period, despite the widespread emission reduction (Huang et al, 2020;Le et al, 2020;Su et al, 2020). For this reason, among others, it is worthwhile extending the in situ verification of the performance of Aeolus wind products to China.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in meteorological parameters and boundary-layer dynamics may significantly affect the amount, types and properties of aerosols and mask the effect of changes in emissions [74,75]. Figure S1 shows the variability in the meteorological parameters at Thissio in spring 2020 (pre-, post-and lockdown periods) compared with those during the previous years.…”
Section: Meteorological Conditions In Athens During the Spring Seasonmentioning
confidence: 99%
“…Ca-ATPase) and secretion of acid-rich proteins 4 . Tracking the state of the carbonate system in the ECM is emerging as a central methodology underpinning a mechanistic understanding of how environmental change, such as ocean acidification, influences skeletal formation and ultimately the growth of these important ecosystem engineers 5 7 .…”
Section: Introductionmentioning
confidence: 99%